Addressing the Drivers of Carbon Emissions Embodied in Indian Exports: An Index Decomposition Analysis. Issue 4 (November 2019) - Banerjee, Suvajit
This study identifies the determinants that have an observable impact over the change in carbon dioxide emissions embodied in the production of Indian exports by adopting an index decomposition analysis to address the contribution from four mutually non-exclusive factors which arise due to India's increasing export performance during the 1995–2009 period on the change in total emissions embodied in exports. These four factors are scale effect, composition effect, emission regulation effect and production efficiency effect. The idea of bringing the last two effects is to capture the impact from technology factor due to international trade. This study found an increased emission embodiment in exports of 234.24 mega-tonnes by using input–output modelling with 'emissions embodied in bilateral trade' approach and then applies the Logarithmic Mean Divisia Index-I (LMDI-I)-based additive and multiplicative formulae following Ang and Zhang (2000) and Ang (2004) to conduct the decomposition exercise. This study finds the scale effect as the largest contributing factor increasing the emission levels by more than 184 per cent of the original increase, while the other three effects creating dampening impact over this scale-driven increase. Emission regulation effects created the maximum cleaning-up impact, especially during the 2002–2009 phase. JEL Codes: C67, F64, Q43, Q48, Q56